Curcumin Reprograms TAMs from a Protumor Phenotype towards an Antitumor Phenotype via Inhibiting MAO-A/STAT6 Pathway - Mingjing Jiang; Ying Qi; Wei Huang; Ying Lin; Bo Li (Cells, 2022)
M1 phenotype macrophages have anticancer characteristics, whereas M2 phenotype macrophages promote tumor growth and metastasis. A higher M1/M2 ratio, therefore, has a beneficial effect on the tumor immune microenvironment, thereby inhibiting tumor growth. The natural alkaloid curcumin is found to have anticancer properties. However, the mechanism remains unclear. In this study, a cell co-culture system and M2 macrophage model were used to evaluate the effects of curcumin on tumor-associated macrophage (TAM) phenotypes. Our results demonstrate that curcumin reprogrammed the M2 macrophages by reducing the level of anti-inflammatory cytokines (TGF-β, Arg-1, and IL-10) and an M2 surface marker (CD206) induced by Cal27 cells or IL-4, as well as upregulating proinflammatory cytokines (TNF-α, iNOS, and IL-6) and an M1 surface marker (CD86). The in vitro assays suggested that curcumin treatment suppressed the migration and invasion of the Cal27 cells induced by the M2-like macrophages. Mechanistically, the repolarization of TAMs may be attributed to the inhibition of monoamine oxidase A (MAO-A)/STAT6 signaling after curcumin treatment. Collectively, our results show that the anticancer effects of curcumin could be explained by reprogramming TAMs from a protumor phenotype towards an antitumor phenotype.